Audit Structure and Its Relation to Role Conflict and Role Ambiguity: An Empirical Investigation - Bamber, E. Michael; Snowball, Doug; Tubbs, Richard M. (The Accounting Review, 1989)
[The trend towards more structure in some of the largest accounting firms' audit methodologies has generated considerable interest, but little empirical evidence. This study provides evidence on the role conflict and role ambiguity perceived by audit seniors in structured versus unstructured accounting firms. Role theory provides a basis for analyzing the effects of audit structure on the organizational characteristics which are potential sources of role conflict and ambiguity. The results are based on a sample of 67 seniors from structured and 54 seniors from unstructured firms. The seniors' perceptions of their firms' organizational characteristics and their perceived role stress differed systematically across structured versus unstructured firms. No evidence is found of the concenrs (such as inflexibility in atypical audit environments) that have been raised regarding the trend towards increasing audit structure.]